2013
DOI: 10.1016/j.clae.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Corneal epithelial permeability: Ethnic differences between Asians and non-Asians

Abstract: a b s t r a c tPurpose: To ascertain whether a difference in the permeability of the corneal epithelium to fluorescein (P dc ) exists between Asians and non-Asians. Methods: From a multi-study database we extracted 632 records of baseline, open-eye P dc measurements taken on both eyes of 176 subjects. Subjects were awake for a minimum of 4 h before measurement, and were free of ocular disease and central corneal staining. P dc was transformed by natural logarithm to better approximate normality for statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…Therefore, variations in the permeability of this tissue can have significant impacts on the safety of contact lens wear 20 and the efficacy of topical medication delivery. 23 Previous studies have shown that Asians who have no history of contact lens wear and no apparent corneal staining with fluorescein dye have higher corneal epithelial permeability when compared with non-Asian subjects. 20,23 According to one study, the inherent ethnicity-related difference, on average, is 27.7%.…”
Section: Corneamentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, variations in the permeability of this tissue can have significant impacts on the safety of contact lens wear 20 and the efficacy of topical medication delivery. 23 Previous studies have shown that Asians who have no history of contact lens wear and no apparent corneal staining with fluorescein dye have higher corneal epithelial permeability when compared with non-Asian subjects. 20,23 According to one study, the inherent ethnicity-related difference, on average, is 27.7%.…”
Section: Corneamentioning
confidence: 99%
“…23 Previous studies have shown that Asians who have no history of contact lens wear and no apparent corneal staining with fluorescein dye have higher corneal epithelial permeability when compared with non-Asian subjects. 20,23 According to one study, the inherent ethnicity-related difference, on average, is 27.7%. 23 Anatomic and physiological differences in eyelid structure have been the most accepted explanations of this inherent difference.…”
Section: Corneamentioning
confidence: 99%
See 3 more Smart Citations